Effects of training program on medicine ball throwing performance in young volleyball players - Battaglia, G.; Bellafiore, M.; Proia, P.; Palma, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It is often recommended that off-season training programs aim to develop muscular strength and power in volleyball players (Marques et al., 2008). However, improvements in performance may be possible with a well-designed training regimen. The purpose of this case report is to study the effects of a specific training program to improve explosive power of upper limbs in young female volleyball players. Methods: In the present study were included twenty one short-limbed girls (Scelic Index .54.6) of which 11 age-matched control sedentary subjects [SS] (age: 15.00+/-0.52 years, BMI: 21.10+/-2.09, SI: 55.45+/-1.45) and 10 volleyball players [VP] (age: 14.50+/-0.97 years, BMI: 22.17+/-1.87, SI: 55.29+/-2.12). SS did not perform any physical activity during the 4-week experimental period. Instead, VP completed 3 training sessions per week, which included specific exercises to improve explosive power of upper limbs and technicaltactical exercises. Over the 4-weeks, athletes performed 2.4 sets of 4.12 repetitions for resistance exercises during each training session (~55 minutes). All sessions were supervised by one of the investigators as well as by the team head coach. Muscular strength and power were assessed before and after the 4-week training program by seated backward overhead ball throw (SBOBT) and seated chest pass throw (SCPT) using a 3-kg rubber medicine ball. All tests were performed for three times but only the best performance was considered. Results We did not show any significant differences in SS` performances during SBOBT and SCPT after 4-weeks. Instead, we found that this specific training program can improve throwing performance in young female volleyball players. Indeed, we showed that VP increased the distance both in SBOBT (P<0.001) and SCPT (P<0.001) after 4-weeks of a specific training program. Discussion: The current findings suggest that this specific training program can improve VP` explosive power during the pre-competition season by implementing a welldesigned training program. However, in agreement with Ha´kkinen et al. (1993) we suggest that in order to maintain the explosive strength, the magnitude of both strength and explosive training stimuli should be given careful attention during the entire course of the competitive season.